Ahbang corporation / Tengku Mohd Izman Tengku Mohd Shah ... [et al.] - Tengku Mohd Shah, Tengku Mohd Izman; Mohd Razip, Mohd Isyraf Qayyum; Tokiman, Muhamad Taqiyuddin; Zakaria, Nizar; Ahmad Mazian, Anas (2016)
The product which is to be developed is a smart umbrella. This smart umbrella is installed with weather forecasting system which can inform the user about the oncoming weather. Compared to the other conventional umbrella, this umbrella has a better design which it eases the users in handling of opening and closing of the umbrella.